Aspects of the fatigue behaviour of acrylic bone cement - Murphy, Bruce Philip (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2002)
Polymethylmethacrylate bone cement is used to fixate many orthopaedic implants. However, it is a brittle material, prone to damage accumulation leading to cement cracking and prosthesis loosening. The damage accumulation failure scenario has been recognised as the predominant mode of cemented implant loosening, and a combination of finite element analysis and continuum damage mechanics can be used to model this failure scenario; however, the empirical laws used to model the fatigue behaviour of acrylic bone cement are incomplete. The objective of this thesis is to develop empirical laws which accurately describe the fatigue behaviour of acrylic bone cement. Furthermore, this thesis addresses a number of aspects of the fatigue behaviour of acrylic bone cement which are relevant to experimental testing and clinical performance. Three experimental tests were designed to investigate a number of aspects of the fatigue behaviour of acrylic bone cement. Namely; the mismatch between the in vivo and in vitro performance of vacuum-mixed cement; the relationship between damage accumulation and stress; the effect of an off-axis tensile stress on the fatigue strength of acrylic bone cement.
Keywords: Mechanical Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin